Study Of The Effectiveness Of The Cultural Practice Of “Balale” (Gotong Royong) Planting Rice Of The Dayak Benyadu Tribe Supporting Family Food Security In Border Area Communities - Eligia Monixa Salfarini; Maya Sari; Nikodemus Talis (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Food security and family welfare will be realized if farmers are able to meet the needs of their families. Local farmers still live the culture in their lives including in farming. One of the local cultures that is still alive in agriculture is the balale culture. Balale culture is carried out by border communities in planting rice together which is their main livelihood. Therefore, it is necessary to examine the effectiveness of balale culture as local wisdom in supporting the food security of local farming families. Using qualitative methods, data were obtained through observation and interviews with participants. The selected participants are local farmers who still apply the belale culture. Data were analyzed using the triangulation method where data were organized, reduced and codified to draw conclusions about the effectiveness of belale culture in supporting the food security of farming families. The results showed that belale culture is still very effective in maintaining the resilience of local farmers and even improving the family economy.